Labor market segmentation and efficient bargaining in a macroeconomic model - Oliver Claas (Bielefeld University, Center for Mathematical Economics (IMW), 2018)
This paper studies the implications of a segmented labor market with efficient wage-employment bargaining on the internal labor market and a competitive external labor market on the temporary equilibrium of a closed monetary macroeconomy of the AS-AD type with government activity, fiat money, and expectations. Workers have identical preferences, those on the internal labor market are represented by a labor union. There is no mobility between the labor markets. Union power measured by the share of the production surplus allotted to the union and union density measured by the fraction of workers who are union members impact the functional income distribution, but neither affect the individual employment levels nor the aggregate employment level and the aggregate supply function. The wage on the internal labor market is above the wage on the external labor market if and only if the profit share of total revenue is smaller than under a fully competitive labor market. Unique temporary equilibria exist for all combinations of union power and union density. The paper provides a complete comparative-statics analysis showing in particular a negative price effect of union power and a positive price effect of union density. In general, the effects of union power and union density on any equilibrium value are usually of opposite signs. Single-labor-market models with a fully competitive or a fully unionized labor market are special or limiting cases of the segmented-labor-market model.
urn:nbn:de:0070-pub-29305975
Keywords: 330